The Implementation of Home Visit Learning to Improve Mathematics Learning Outcomes during the COVID-19 Pandemic for Students at SDN 239 Inpres Rembon, Tana Toraja - Oktavia Mangalik; Mas'ud Badolo; Idha Novianti (PT ARRUS Intelektual Indonesia, 2023)
This research is to describing the implementation of home visit learning to improve mathematics learning outcomes for students at SDN 239 Inpres Rembon, Tana Toraja Regency during the covid-19 pandemic. This study uses a descriptive approach with the type of case study research. The research subjects were selected using a purposive technique, namely grade 4 teachers and students. Data collection in the field was done by interview, observation, and documentation. While the validity of the data using triangulation techniques. The results of the study show that student learning outcomes during the Covid-19 pandemic with limited face-to-face learning are still lacking. Home visit learning planning is based on the problems faced by students in learning mathematics during the Covid-19 pandemic. The implementation of home visit learning begins with careful preparation, then the implementation of learning is carried out in accordance with the lesson plans prepared by the previous teacher. Home visit evaluation learning is carried out according to the assessment in the lesson plan, namely through the assessment of attitudes, knowledge and skills. There are obstacles faced by teachers in learning home visits. The weather factor is the main obstacle in the implementation of home visit learning at SDN 239 Inpres Rembon.